Morphometric assessment of the red stripe weevils, Rhynchophorus vulneratus (Coleoptera: Curculionidae) from several localities in Malaysia - Sazali S.N.; Hazmi I.R.; Rahim F.; Abang F.; Jemain A.A. (American Institute of Physics Inc., 2024)
The recognition of intraspecific variation could enhance knowledge and understanding on the population divergence that might be resulted from different geographical areas. To study the possible effect derived from different locations, a morphometric study of the red stripe weevils, Rhynchophorus vulneratus from different localities in Malaysia was conducted using field and voucher specimens. A total of twenty-Three morphological characters were examined from 108 individuals of R. vulneratus representing population of Kota Samarahan, Mukah and central of Peninsular Malaysia. The data were subjected to univariate one-way single factor analysis of variance (ANOVA) and analysed in factor analysis using SPSS version 22.0 software. Univariate ANOVA showed that all tested variables were significantly different (p<0.05) except for mesocoxal distance (MSD), meanwhile from the factor analysis, the first three factors with eigenvalues greater than 1.0 were successfully extracted, resulting in a high variation of 82.687%. For factor 1, 39.213% of total variation was recorded, factor 2 accounted for 34.096% and factor 3 contributing to 9.377%, respectively. The mixed plotting among the twenty-Three morphological characters suggests a strong correlation among the parameters examined and further statistical analysis should be conducted to include environmental factors such as habitat types, food availability and predation effect. 2018 Author(s).